The Analysis on Figurative Language in Harry Styles’ Harry's House Album - Saputris, Dhayun (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2025)
Figurative Language uses words to explain or express complex meanings that are not easy to imagine. Figurative Language often uses comparisons so that the meaning or description of something can be expressed well in literature artworks such as poetry, books, poems, and even songs. Figurative Language contains hidden meanings in it, especially in song lyrics. Figurative Language makes the listeners understand the song's meaning and messages, then make a song more beautiful and variable. This research aims to find out the kinds of figurative language used in song lyrics entitled Harry’s House album by Harry Styles. The object of the research is song lyrics, especially in Harry’s House Album, which contains 13 songs. The research method used in this research is descriptive qualitative. The data is collected from spoken and written words as well as observing behaviour. The data analysis is by identifying and classifying through the song lyrics, then analyzing it into the kinds of figurative language by using Kennedy’s theory as guidance. The final result of this research is that there are 10 kinds of figurative language used through song lyrics in Harry’s House album by Harry Styles. They are Personification, Simile, Metaphor, Hyperbole, Paradox, Irony, Metonymy, Synecdoche, symbolism, and Allusion. Moreover, the most used figurative language in song lyrics is metaphor. There are 12 songs used metaphor as figurative language through it.